SERVICES QUALITY AS A FACTOR FOR PREVAILING THE DIFFERENCE BETWEEN EXPECTED AND PERCEIVED SERVICES IN AGENCY BUSINESS - Jocić, Lidija; Vujko, Aleksandra; Panić, Aleksa (The Business of Tourism, 2024)
The paper is based on the assumption that quality service is a factor in achieving competitive advantage and positioning on the tourist market of agency business, and that quality is achieved through a series of relationships in the tourist-employee relationship. If the employee treats the tourist with respect, provides accurate and reliable information and exceeds the tourist's expectations with the service provided, he will get a loyal guest who will, based on the "mouth to mouth" system, spread positive experiences to the others, so they will also become travelers of the agency. If we look at tourism as a "factory" of experiences, it is clear that for an extremely positive experience, it is necessary that every link in the series of providing a complex tourist service is of high quality. The first in a series of links is certainly the tourist agency. The modified SERVQUAL model led to the conclusion that tourists who traveled with the Asturs agency received adequate "value for money", that is, that the service provided by the agency was of better quality than expected.
Keywords: agency business; quality; service; SERVQUAL model